FOOD SAFETY AND EATING HABITS DURING PANDEMIC COVID-19 IN THE REPUBLIC OF SERBIA - Zrnic, Milos; Kilibarda, Nataša; Brdar, Ivana; Vujić, Milan; Stojanović, Djordje (Economics of Agriculture, 2021)
Food safety is of paramount importance at all times, especially in exceptional circumstances, such as pandemic COVID-19, given the fact that coronavirus is spreading rapidly and little is known about coronavirus. Protections have been strengthened in all fields, including food safety. In order to best protect ourselves and others, it’s necessary to handle food properly, especially if children, pregnant women, the elderly and the ill ones are in the immediate vicinity. The paper will examine food safety and eating habits during pandemic COVID-19, with focus on recommended guidelines for safe food preparation, food storage, together with the prescribed measures of the Government of the Republic of Serbia.